2021
DOI: 10.1101/2021.04.08.438911
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nanobody Repertoires for Exposing Vulnerabilities of SARS-CoV-2

Abstract: Despite the great promise of vaccines, the COVID-19 pandemic is ongoing and future serious outbreaks are highly likely, so that multi-pronged containment strategies will be required for many years. Nanobodies are the smallest naturally occurring single domain antigen binding proteins identified to date, possessing numerous properties advantageous to their production and use. We present a large repertoire of high affinity nanobodies against SARS-CoV-2 Spike protein with excellent kinetic and viral neutralizatio… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 132 publications
(114 reference statements)
0
15
0
Order By: Relevance
“…The mutational sensitivity map also shed some light on structure-functional role of sites targeted by common resistant mutations (F490S, E484K, Q493K, F490L, F486S, F486L, and Y508H) that evade many individual nanobodies. 47 Indeed, we found that E484, F486, and F490 positions can be sensitive to Nb6 binding (Figure 4A-C), while variations in these sites are known to have only minor effect on ACE2 binding.…”
Section: Resultsmentioning
confidence: 83%
See 3 more Smart Citations
“…The mutational sensitivity map also shed some light on structure-functional role of sites targeted by common resistant mutations (F490S, E484K, Q493K, F490L, F486S, F486L, and Y508H) that evade many individual nanobodies. 47 Indeed, we found that E484, F486, and F490 positions can be sensitive to Nb6 binding (Figure 4A-C), while variations in these sites are known to have only minor effect on ACE2 binding.…”
Section: Resultsmentioning
confidence: 83%
“…46 Another diverse repertoire of high affinity nanobodies against SARS-CoV-2 S protein that are refractory to common escape mutants and showed synergistic neutralizing activity are characterized by proximal but non-overlapping epitopes suggesting that multimeric nanobody combinations can improve potency while minimizing susceptibility to escape mutations. 47 These studies identified a group of common resistant mutations in the dynamic RBM region (F490S, E484K, Q493K, F490L, F486S, F486L, and Y508H) that evade many individual nanobodies. 47 Structural versatility of nanobody combinations that can effectively insulate the S-RBD accessible regions suggested a mechanism of resistance to mutational escape in which combining two nanobodies can markedly reduce the number of allowed substitutions to confer resistance and thereby elevate the genetic barrier for escape.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This would obviously imply that different spike regions are simultaneously recognized by polyclonal anti-spike antibodies of different specificity, elicited by the virus (or by a vaccine) in each patient. Moreover, a variable proportion of the elicited antibodies may be directed against largely invariable spike regions, i.e., protein regions whose mutational change would severely impair the fitness of the virus (14)(15)(16)(17)(18). Thus, loss of immune-recognition of a certain spike region caused by a mutational event, should, in principle, be compensated by the persistent recognition of the virus by antibody molecules directed against spike regions that have not changed or that are intrinsically not permissive to amino acid substitutions because of structural or functional constraints.…”
mentioning
confidence: 99%